Systematization and evaluation of data processing methods for determining the state and structure of complex objects - Жук, Л. О.; Сураєв, В. Ф. (Proceedings of National Aviation University (archive), 2021)
Methods of spectrometric data processing are systematized, effective computer procedures for quick rapid analysis of the state or structure of complex objects during large-scale experiments, providing technological processes or research sciences are substantiated